Autopilot and guidance law design considering impact angle and time. Issue 2 (1st January 2018) - Wang, Xianghua; Tan, Chee Pin; Zhou, Donghua
Abstract : The authors propose an autopilot based on partial integrated guidance and control for missiles to achieve interception at a pre‐specified impact angle and a close approximation of impact time. The scheme has an outer loop comprising the engagement model and slow dynamics (to generate a pitch‐rate command that causes the missile to establish a collision course with the target), and an inner loop comprising the fast dynamics (to make the pitch rate track its command signal). The authors divide the missile flight into two phases; in the first phase the controller causes the missile line‐of‐sight (LOS) angle (impact angle) to converge to the pre‐specified value at a pre‐specified time, and to remain there thereafter (and hence establishes a collision course at the desired impact angle). In the second phase, the missile will fly along the LOS until interception occurs. The authors also provide an estimated calculation of the impact time and give the factors that influence the estimate, which helps the user systematically choose the missile parameters in order to achieve a certain impact time; this result can be applied to the case of salvo attack of multiple missiles without online data links. Finally, simulations are performed to verify the scheme effectiveness.